Ateromatic injuries in cardiovascular and brain arteries in adolescent population and young adult (post mortem): Tacna Region, Peru - Arias Santana, Victor (2020)
To establish a basis for the current state of damage to arteries through pathological classification in post-mortem samples. Objective: To observe and compare the structural changes in the aortic, cardiovascular carotid, and coronary and posterior basilar cerebral arteries, in corpses of people aged 15 to 35 years. Method: Observational and analytical, prospective cross-sectional study in the field of public health. We worked with 24 bodies according to inclusion and exclusion criteria. Arterial damage was classified according to the American Heart Association. Results: In the aorta, the injuries were type I (45.8%), 8.3% had a type II, III, IV injury, respectively. In the 15-19 age group, 60% had type I injuries. In the carotid, 62.5% had a type I injury and 12.5% a type II injury. 100% of the group aged 15 to 19 had a type I carotid injury. In the coronary artery, 75% had type I injuries, 12.5% with type II injuries. In the group of 15 to 19 years, no coronary sample was healthy. In the basilar artery, 33.3% had type I lesions, being more frequent in the group of 20 to 29 years (44.4%). In general, type I lesions were observed more in the coronary (72%), type II coronary and carotid (12%), type III in the aorta (8%) and type IV in the aorta (8%). Conclusion: Structural damage to arteries begins at an early age and differs according to arterial location.